Analisis Kinerja Sistem MIMO-OFDM pada Kanal Rayleigh dan AWGN dengan Modulasi QPSK - M. Lukmanul Hakim; Sukiswo Sukiswo; Imam Santoso (Transmisi: Jurnal Ilmiah Teknik Elektro, 2012)
OFDM (Orthogonal Frequency Division Multiplexing) is a transmission technique uses multiple frequencywhich each carrier is orthogonal. Each sub-carriers are modulated with a conventional modulation technique at a low symbol rate. This modulation can be modulated Phase Shift Keying (PSK).Problem of interference or multipath fading can be handled withMIMO (Multiple Input Multiple Output). This system uses a number of antennatransmitterand receiverto make the signal reflection as the main signal amplifier so that will support each other . This final project ​​simulates performance of MIMO-OFDM  with Alamouti STBC (Space Time Block Code) and MRC (Maximal Ratio Combining) withQPSK modulation at Rayleigh Fading Distribution Channel and AWGN (Additive White Gaussian Noise). The simulation results shows it need s Eb/No = 5dB to achieve BER = 10-5in both MIMO techniques.BER = 0 when Eb/No greater than 5 dB at STBC and BER = 0 when Eb/No greater than 5 dB at STBC . Better BER of MIMO STBC than MIMO MRC  found on almost all values ​​of Eb/No. Based on the simulation,  performance ofSTBC-OFDM technique have advantages 1 dB fromMRC-OFDM technique to achieve BER = 0. Keyword :   OFDM, STBC, MIMO, BER